(untitled) (Bangladesh Journal of Zoology, 2016)
The ovicidal and repellent effects of 11 spice powders against the pulse beetle Callosobruchus chinensis L. and C. maculatus (F.) (Coleoptera: Bruchidae) on stored chickpea and black gram, respectively was investigated. The spice powders of black cumin, black pepper, cinnamon, clove, coriander, cumin, green cardamom, large cardamom, nutmeg, red pepper and Trigonella were used throughout the experiment. The data were recorded on oviposition after 30, 60 and 100 days and repellent activity after 1 to 5 hours of treatment doses of 25 and 37.5 mg/g spice powders, which were applied with chickpea and black gram seed on C. chinensis L. and C. maculatus (F.), respectively. Minimum number of oviposition was observed in black pepper, clove and cinnamon treated pulses, while maximum number was recorded in control treatments. The ovicidal activity of the spice powders was in the order of black pepper > clove > cinnamon > nutmeg > black cumin > cumin > green cardamom > red pepper > coriander > large cardamom > Trigonella> as control for C. chinensis L. and black pepper> clove> cinnamon> nutmeg> black cumin> cumin> green cardamom> red pepper> coriander> Trigonella> large cardamom> as control for C. maculatus (F.). Black peeper, clove, cinnamon and nutmeg showed repellant activity against adult C. chinensis L., and black peeper, clove and cinnamon showed repellant activity against adult C. maculatus (F.) while the others spices did not show any repellency. Bangladesh J. Zool. 44(1): 51-59, 2016